Analisis Pemanfaatan Media Sosial Dalam Meningkatkan Penjualan Lanatashop_10 Di Kecamatan Ledo, Kalimantan Barat - Natalia, Lanata; Atlantika, Yeremia Niaga (Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
This research aims to understand the utilization of social media in enhancing the sales of Lanatashop_10. The study was conducted on the Lanatashop_10 business in the Ledo sub-district, Bengkayang regency, West Kalimantan. The research employed a qualitative approach with a descriptive research method, utilizing both primary and secondary data sources obtained through observation, in-depth interviews, and documentation, followed by data processing leading to conclusions. The findings indicate that social media plays a significant role in increasing the sales of Lanatashop_10. Consumers appreciate a variety of products that keep up with the times, prompting society to stay updated, especially in the fashion world, which is widely favored by adults and teenagers alike. Social media has a positive impact on business owners, enabling them to expand their business networks and target markets. The increase in sales serves as a benchmark for business owners to determine whether their efforts are on the rise or decline.